Reforma del artículo 576 del código de trabajo en cuanto a la obligación de contestar la demanda por escrito - Tocto Sarango, Wilson Marcelo (2015)
Within the practice, lawyers sponsors introduced in labor cases Judicial Units of Labor are made according to Article 576 of the Labor Code Speaking at the Preliminary Settlement Hearing and Statement of Defense Test Annunciation, the time to answer the complaint in writing as imperatively as provided in said Article. It is noted that from an institutional vision that the process should be given to labor processes under Ecuadorian ordinary legislation is the oral procedure , in accordance with the Act 13-2003 , amending the Labor Code published in Official Gazette No. 146 of August 13, 2003 and its amendments , Article 576 of the current Labor Code deals with Preliminary hearing Conciliation answer to the application and formulation of evidence, determines that it must be oral, where the judge will seek conciliation between the parties and not having step will be the defendant to answer the same demand without prejudice oral presentation, the respondent shall file its reply in writing. In this context an anomalous behavior that violates the principle of orality established in the Constitution of the Republic of Ecuador and determines that all judgments be governed by this principle arises. The provisions of Article 576 of the subject of the present Labor Code development research is unfounded and transgresses the provisions of the Constitution of the Republic of Ecuador and other laws or regulatory bodies of law. This problem is compounded by the lack of rules and reforms to criminalize a true oral procedure within work processes that enable Lawyers for free exercise of the profession to sponsor within the scope causes labor to make their presentations within the Preliminary Hearing Conciliation answering the application and formulation of evidence orally thereby complying with the legal principles established in the Constitution of the hierarchically superior to the standard Republic Ecuador's legal system.